ECONOMIC CLUSTERS BASED ON THE POTENCY AND REGIONAL CHARACTERITICS IN THE CITY OF KENDARI - R Marsuki Iswandi; Laode Alwi; Dasmin Sidu (Diponegoro University, 2011)
Kendari city is one of the autonomous regions in Southeast Sulawesi province, so Kendari continues to improve its economic growth. Although as a city, the economic activities in Kendari still has the characteristics of the livelihoods of rural population is engaged in the production of primary sectors such as agriculture and fisheries. The purpose of this study is to determine the pre-eminent economic clusters based on characteristics of the districts in Kendari and generate superior economic cluster map.The research was conducted from July to Sep-tember 2010 in all districts in Kendari. That is descriptive quantitative research methods, analysis techniques used in determining the basis of economic analysis Quotient Location (LQ) and to determine the economic contribution of each sector were analyzed descriptively supe-rior.The results showed that in accordance with the potency and characteristics of the districts in Kendari there are four leading economic clusters: (1) agriculture cluster (crops, horticulture and plantation), covering several villages in the Abeli district , Poasia district, Man-donga district and Puuwatu district ; cluster and marine fisheries (aquaculture and capture fisheries), covering several villages in the Abeli district, and Poasia district and Kendari district, (3) industry clusters, (a) the industrial processing of fishery and agriculture include Abeli district, Poasia district, Kendari district and Western Kendari district, (B) food and beverage industry include Kendari district and West-ern Kendari district , (c) furniture and handicraft industries include Baruga district, Kadia district, and Puuwatu district. Cluster servicesand trade covers several villages in Mandonga district, Wua-Wua district, Kadia district, Kendari district, Kambu district and Baruga district.